The Palgrave Handbook of Global Migration in International Business - Mockaitis, Audra I. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This handbook focuses on the dynamic nature of global migration and its implications for international business. Migration shapes the societal and organizational contexts of international business; yet studies on migration have only recently become more prominent. For example, the existence of multinational enterprises (MNE's) depends to no small extent on the mobility of people; MNE's source, develop, deploy, and utilize global talent. This talent pool includes, but is not limited to, skilled expatriates or corporate migrants, as well as culturally and ethnically diverse workforces comprised of first- and second-generation migrants, highly skilled refugees that help organizations enhance their legitimacy in host countries, and returnee immigrants encouraged by changing home country conditions. Added to that, global events such as the COVID-19 pandemic and Brexit have introduced new and far-reaching challenges for international firms in managing their international workforces and international mobility. Meanwhile, at the individual level, these issues are compounded for migrants having to cope with multiple work and non-work demands. Chapters in this handbook offer both firm and migrant perspectives, covering topics such as diaspora networks in international alliances, migrant careers, and migrant re-entry issues, among others. Split into five sections, this handbook covers the whole spectrum of issues, thus furthering our understanding of this increasingly important topic. Chapters in this handbook offer both firm and migrant perspectives, covering topics such as diaspora networks in international alliances, migrant careers and migrant re-entry issues, among others. Split into five sections, this handbook covers the whole spectrum of issues, thus furthering our understanding of this increasingly important topic. .
1. Introduction -- Section 1: Theme: Migration landscapes and the consequences of the pandemic for migrants and international business.-2. The pandemic, vulnerable migrants and international business: A vicious cycle -- 3. Unpacking the complexities of migrant work through the pandemic: Zooming in on the agricultural industry in New England. 4. - Expatriates within the pandemic: Two sides of the same coin -- 5. - Organizational factors influencing the professional well-being of self-initiated expatriates during the COVID-19 pandemic. 6. -The salience of cultural differences due to the COVID-19 pandemic -- 7. Social contagion in emigration decisions: Evidence from South Africa -- Section 2: Migrants as an international business resource -- 8. Leveraging transnational social capital: shared perspectives in migration and global mobility -- 9. Female diasporans and diaspora networks: A neglected resource for business? -- 10. Career capital of self-initiated expatriates (skilled migrants) -- 11 - International career success factors across multi-levels: Focusing on best practice -- 12. -The critical link between organizational identification and organization-based self-esteem for migrant innovativeness -- 13. Online support and inclusion of international workers -- 14. Motility of international IT workers : beyond the myth of digital nomads -- 15. Migrant returns to organisations in Central and Eastern Europe: Challenges with skill transfers -- Section 3. Migrants' Language and Culture: Implications for International Business -- 16. The pervasive influence of migrants' language skills on SME internationalization: A literature review -- 17. Leveraging from the cultural mix: A study of Finnish migrant entrepreneurs in Florida -- 18. Dissecting generations of migrant identities within a diaspora -- 19. Value differences between Lithuanian emigrants in the main destination countries and not migrated Lithuanians -- 20. Conclusion.
Keywords: International business enterprises; Emigration and immigration -- Social aspects; International Business; Sociology of Migration